Solid-state fermentation of brewer's spent grain for xylanolytic enzymes production by Penicillium janczewskii and analyses of the fermented substrate - César Rafael Fanchini Terrasan; Eleonora Cano Carmona (Bioscience Journal, 2015)
In recent decades, increasing interest has been devoted to xylanolytic enzymes due to their potential use in many industrial processes. This study describes the production of xylanase, Î²-xylosidase and Î±-L-arabinofuranosidase, belonging to the xylanolytic complex, by Penicillium janczewskii using brewer's spent grain as substrate for solid-state fermentation. The optimized conditions for high levels of xylanase, Î²-xylosidase and Î±-L-arabinofuranosidase production were: 50% initial moisture, which was provided by Vogel's salt solution, seven days of cultivation at 20-30 °C. Fermentation enriched the bioproduct with some amino acids but did not add mycotoxins to it The use of brewer's spent grain as substrate for fungal cultivation and enzyme production can both add value to this waste and reduce the production cost of xylanolytic enzymes.